Ground ice as indicator of the Pleistocene history of the Russian Arctic - N. A. Shpolyanskaya (Лëд и снег, 2015)
Based on the analysis of massive ground ice origin, the geological development of the Russian Arctic in the Quaternary period has been considered. A classification of massive ice with two new genetic types (submarine and coastal-marine) and new mechanism of their formation have been proposed by the author. The possibility of permafrost formation with massive ice directly in marine environments has been calculated. Significant differences in the geological development of western and eastern Arctic, particularly in the transgressive-regressive mode, have been revealed. This calls into question the leading role of glacial eustatic processes in sea level fluctuations and brings to the fore the role of tectonic processes.